2007
DOI: 10.1002/mrd.20809
|View full text |Cite
|
Sign up to set email alerts
|

Efficient propagation of single cells accutase‐dissociated human embryonic stem cells

Abstract: Human embryonic stem cells (hESCs) hold great promise for cell-based therapies and drug screening applications. However, growing and processing large quantities of undifferentiated hESCs is a challenging task. Conventionally, hESCs are passaged as clusters, which can limit their growth efficiency and use in downstream applications. This study demonstrates that hESCs can be passaged as single cells using Accutase, a formulated mixture of digestive enzymes. In contrast to trypsin treatment, Accutase treatment do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 20 publications
3
107
0
1
Order By: Relevance
“…Second, we used Accutase (a mixture of proteolytic and collagenolytic enzymes) to dissociate the cells. It has been reported that using Accutase instead of trypsin can significantly improve cell viability (Bajpai et al 2008). Third, we treated cells with a ROCK (Rho-associated kinase) inhibitor before and during transfection.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we used Accutase (a mixture of proteolytic and collagenolytic enzymes) to dissociate the cells. It has been reported that using Accutase instead of trypsin can significantly improve cell viability (Bajpai et al 2008). Third, we treated cells with a ROCK (Rho-associated kinase) inhibitor before and during transfection.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have reported that recombinant vitronectin 12 , a hydrogel 13 , and a LN-511 fragment 14 can serve as alternatives to Matrigel or feeder cells for culturing of hES cells. However, none of the cell culture substrata allows clonal survival of hES cells without the use of apoptosis inhibitors [15][16][17] or chemically undefined substances 18,19 , and the cells are often passaged in small clumps that can contain a significant proportion of differentiated cells. Since the initial number of cells is low during derivation of new ES cell lines, absence of cell culture conditions that enable clonal survival also complicates the derivation procedure especially from single blastomeres.…”
mentioning
confidence: 99%
“…Most of the surface proteins will be destroyed by Trypsin detachment during the procedure. Trypsin needs to be actively inactivated to stop the reaction [16]. Similarly, the cytotoxic effect may also be present by the use of detergents [17,18].…”
Section: Discussionmentioning
confidence: 99%